Assessing the impact of contraceptive use on reproductive cancer risk among women of reproductive age—a systematic review - Jahanfar, Shayesteh; Mortazavi, Julie; Lapidow, Amy; Cu, Cassandra; Al Abosy, Jude; Morris, Kathyrn; Becerra-Mateus, Juan Camilo; Steinfeldt, Meredith; Maurer, Olivia; Bohang, Jiang; Andrenacci, Paola; Badawy, Marwa; et al. (Frontiers in Global Women's Health, 2024)
BackgroundContraceptives play a crucial role in women's reproductive health, their hormonal components may be linked to cancer risks, specifically breast, and gynecological cancers. Given the high usage rates of hormonal contraceptives, it is vital to systematically evaluate their potential impact on cancer outcomes, especially among women with a family history of gynecological cancers.ObjectivesThis study aims to evaluate the evidence on the association between modern contraceptive use and the risk of breast and reproductive cancers (ovarian, endometrial, and cervical cancer) among women of reproductive age, to inform healthcare providers, women, and program managers about cancer outcomes related to contraceptive use.MethodsA systematic review was conducted according to PRISMA guidelines. Searches were performed in databases such as CINAHL, OVID Medline, EMBASE, and more from inception to February 2022. Eligible studies included randomized controlled trials, cohort studies, and case-control studies that compared cancer outcomes between contraceptive users and non-users. Data extraction, quality assessment, and meta-analyses were conducted following predefined protocols. Subgroup and sensitivity analyses examined variations in contraceptive methods, doses, and duration.ResultsA total of 51 studies were included, comprising 2 RCTs and 49 observational studies. The review identified a significant reduction in ovarian and endometrial cancer incidence among contraceptive users. Hormonal contraceptive users had a 36% lower risk of ovarian cancer (RR 0.64, 95% CI 0.60–0.68), with specific reductions seen in combined oral contraceptive users (RR 0.62, 95% CI 0.57–0.68) and hormonal IUD users (RR 0.68, 95% CI 0.48–0.96). The rate ratio of cervical cancer was higher among non- users compared to hormonal contraceptive users when we pooled the results (1.28, 95% CI 1.21, 1.35). No significant association was found between contraceptive use and breast cancer risk among healthy women (RR 1.00, 95% CI 0.94–1.06). However, BRCA1/2 mutation carriers using oral contraceptives showed a heightened risk of breast cancer (HR 1.39, 95% CI 1.15–1.67).ConclusionThis systematic review highlights the protective effects of modern contraceptives against ovarian and endometrial cancers while identifying an increased risk of cervical. No significant breast cancer risk was found for healthy women, but BRCA1/2 mutation carriers faced increased risks. These findings underscore the need for personalized contraceptive counselling that considers cancer risk factors. Further research is needed to explore contraceptive impacts across different genetic profiles and dosing regimens.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, Prospero (CRD42022332647).